Factors affecting the achievement of fertility intentions in urban Nigeria: analysis of longitudinal data - Stella Babalola; Olamide Oyenubi; Ilene S. Speizer; Lisa Cobb; Akinsewa Akiode; Mojisola Odeku (BMC, 2017)
Abstract Background Maternal mortality ratio in Nigeria is among the highest in the world with an estimated 160 women dying every day of complications related to pregnancy and childbirth. In addition to appropriate management of complications related to pregnancy and childbirth, preventing unwanted pregnancies is an effective way to reduce maternal deaths. Identifying potentially modifiable factors associated with the achievement of fertility intentions is critical for developing behavior change interventions that will contribute to reducing maternal mortality. Methods The data analyzed came from a longitudinal design with data collected in 2010/2011 and 2014 from the same group of women of reproductive age in six Nigerian cities. The data were collected as part of efforts to evaluate the effects of the Nigerian Urban Reproductive Health Initiative (NURHI). A total of 10,672 women were interviewed at the two points in time but the analyses in this manuscript were limited to 1921 in-union women who reported that they desired no more children at baseline in 2010/2011. The principal analytic method was multivariable regression adjusted for clustering at the enumeration area level. The analysis controlled for socio-demographic and household variables, ideational characteristics, and contraceptive use at baseline. Results About two thirds of the women who desired no more children at baseline have neither had any children nor were pregnant at endline. The strongest predictors of the achievement of fertility intentions include parity, age, religion, residence, spousal communication about family size, perceived severity of another pregnancy, and spousal agreement about family size. Conclusion A comprehensive strategy to help women avoid unwanted pregnancies should include efforts to increase women's understanding about effective ways to prevent unplanned pregnancies and strengthen self-efficacy for contraceptive use. Promoting spousal communication about reproductive issues, engaging men, promoting smaller family sizes and changing pronatalist attitudes should also be part of such a strategy.